2013
DOI: 10.1016/j.freeradbiomed.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial glutathione depletion reveals a novel role for the pyruvate dehydrogenase complex as a key H2O2-emitting source under conditions of nutrient overload

Abstract: Once regarded as “byproducts” of aerobic metabolism, the production of superoxide/H2O2 is now understood to be a highly specialized and extensively regulated process responsible for exerting control over a vast number of thiol-containing proteins, collectively referred to as the redox-sensitive proteome. Although disruptions within this process, secondary to elevated peroxide exposure, have been linked to disease, delineation of the sources and mechanisms regulating increased peroxide burden remain poorly defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 30 publications
(51 reference statements)
3
110
2
Order By: Relevance
“…However, recent work by our group and others found that it serves as a GSH and GSSG sensor much like OGDH (O'Brien et al, 2017). Using purified PDH and permeabilized muscle fibers, Fisher-Wellman and coworkers found that depletion of glutathione pools or inhibition of NADPH production augmented pyruvate-driven O 2˙− / H 2 O 2 production (Fisher-Wellman et al, 2013. It was then postulated by the same group that PDH was able to sense changes in mitochondrial redox buffering capacity, potentially through S-glutathionylation, which alters ROS production (Fisher-Wellman et al, 2013).…”
Section: -Oxoglutarate Dehydrogenase and Pyruvate Dehydrogenasementioning
confidence: 97%
See 1 more Smart Citation
“…However, recent work by our group and others found that it serves as a GSH and GSSG sensor much like OGDH (O'Brien et al, 2017). Using purified PDH and permeabilized muscle fibers, Fisher-Wellman and coworkers found that depletion of glutathione pools or inhibition of NADPH production augmented pyruvate-driven O 2˙− / H 2 O 2 production (Fisher-Wellman et al, 2013. It was then postulated by the same group that PDH was able to sense changes in mitochondrial redox buffering capacity, potentially through S-glutathionylation, which alters ROS production (Fisher-Wellman et al, 2013).…”
Section: -Oxoglutarate Dehydrogenase and Pyruvate Dehydrogenasementioning
confidence: 97%
“…Using purified PDH and permeabilized muscle fibers, Fisher-Wellman and coworkers found that depletion of glutathione pools or inhibition of NADPH production augmented pyruvate-driven O 2˙− / H 2 O 2 production (Fisher-Wellman et al, 2013. It was then postulated by the same group that PDH was able to sense changes in mitochondrial redox buffering capacity, potentially through S-glutathionylation, which alters ROS production (Fisher-Wellman et al, 2013). However, based on the experimental design it was unclear whether or not PDH was actually sensing any changes in mitochondrial redox buffering capacity or if the increase was simply due to the CDNB-mediated depletion of glutathione pools.…”
Section: -Oxoglutarate Dehydrogenase and Pyruvate Dehydrogenasementioning
confidence: 99%
“…This glutathionylation can increase ROS generation from the E3 subunit since FAD cannot be oxidized by the lipoic acid moiety and reduces O2 by one electron to produce superoxide. Importantly, glutathionylation decreases ROS production when pyruvate is being oxidized, and depletion of glutathione leads to increased ROS production from PDH (71). PDH has also been shown to interact with Grx2 suggesting that the reversible glutathionylation regulates PDH through similar mechanisms to OGDH (70).…”
Section: Lipoic Acid and Ros Generation From Mitochondrial 2-ketoacidmentioning
confidence: 99%
“…, branched-chain 2-oxoacid dehydrogenase (BCKDH) complex (22), and pyruvate dehydrogenase (PDH) complex (20,23). Proline dehydrogenase has also been implicated (24).…”
mentioning
confidence: 99%
“…However, other sites within the matrix can also be important producers of superoxide/H 2 O 2 under these conditions (19,20,23). Together with site I F , these matrix sites (including the OGDH, BCKDH, and PDH complexes) comprise the NADH/NAD ϩ isopotential group, i.e.…”
mentioning
confidence: 99%